2009
DOI: 10.3858/emm.2009.41.7.057
|View full text |Cite
|
Sign up to set email alerts
|

Lotus (Nelumbo nuficera) flower essential oil increased melanogenesis in normal human melanocytes

Abstract: In this study, the essential oil from lotus flower extract, including petals and stamens, was assessed with regard to its effects on melanogenesis in human melanocytes. The lotus flower essential oil was shown to stimulate melanin synthesis and tyrosinase activity in a dose-dependent manner. The lotus flower essential oil induced the expression of tyrosinase, microphthalmia-associated transcription factor M (MITF-M), and tyrosinase-related proten-2 (TRP-2) proteins, but not tyrosinase mRNA. Moreover, it increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…The essential oil that is extracted from Vitex negundo Linn leaves has been reported to possess antioxidant and antimelanogenic activities [20]. By contrast, it has been demonstrated that the lotus flower essential oil stimulates melanin synthesis and tyrosinase activity in normal human melanocytes [21]. The C. cassia essential oil (CC-EO) has hypouricemic [22] and antifungal activities [23]; however, little information is available regarding the inhibitory action of CC-EO on tyrosinase activity and melanogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil that is extracted from Vitex negundo Linn leaves has been reported to possess antioxidant and antimelanogenic activities [20]. By contrast, it has been demonstrated that the lotus flower essential oil stimulates melanin synthesis and tyrosinase activity in normal human melanocytes [21]. The C. cassia essential oil (CC-EO) has hypouricemic [22] and antifungal activities [23]; however, little information is available regarding the inhibitory action of CC-EO on tyrosinase activity and melanogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This denotes that Tunisian aromatic plants can induce melanogenesis in B16 melanoma cells without causing transformation. Later on Jeon [5] studied the essential oil from lotus flower extract and its effects on melanogenesis in human melanocytes. It was found that the effective compound of lotus flower oil palmitic acid methyl ester induced the expression of tyrosinase, microphthalmia-associated transcription factor M Volume 2 Issue 1 -2017 (MITF-M), and tyrosinase-related proten-2 (TRP-2) proteins, but not tyrosinase mRNA.…”
Section: Effect Of Herbal Extract and Their Actives On Melanogenesismentioning
confidence: 99%
“…Interestingly, many natural products contain palmitates. A palmitic-acid ester in oil from the lotus flower (Nelumbo nuficera) enhances melanin production when added to melanocytes grown in vitro 16 . Coconut oil is also rich in palmitates.…”
Section: Red Alert About Lipid's Role In Skin Cancermentioning
confidence: 99%